Local Voices for Cocoa Production: Experiences of Ghanaian Cocoa Farmers on Community Radio - Fred Ankuyi; Enoch Kwame Tham-Agyekum; John-Eudes Andivi Bakang; Nicholas Quayson; Derick Okantah; Treve Hope; Joash Osei-Nyarko; Ross Richmond Wesley (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Local radio has played a significant role in keeping local cocoa farmers informed about their farming activities. However, the experiences of these local farmers who should be the real owners of community radio have not been captured. It would be possible to increase cocoa production if the experiences of local cocoa farmers were given the attention needed. Using a quantitative research approach, the multi-stage sampling technique was used to select 385 respondents. Data were analyzed using frequencies, percentages, means, standard deviations and Kendall’s coefficient of concordance. Results show that farmers were undecided about their reliance on community radio and the role it plays in disseminating agricultural information. However, they understood the agricultural-related information disseminated on community radio. They agreed that the content and presentation of community radio programs were suitable for them but were undecided on the transmission quality and community involvement. Interference from local leaders was the most severe challenge facing farmers’ use of community radio. In order to improve extension delivery there is a need for policymakers and agricultural extension stakeholders to implement programs that will encourage farmers to set up and rely on community radio as a great alternative source of information for their farming activities. This is also necessary to improve the currently low contact of extension agents with farmers, thus, reducing the extension farmer ratio.